New species of Hexabdella and Neomolgus (Acari: Prostigmata: Bdellidae) from Iran - Eghbalian, Amir Hossein; Khanjani, Mohammad; Safaralizadeh, Mohammad Hassan; Ueckermann, Edward A. (Zootaxa, 2016)
A new species of Hexabdella Van der Schyff, Theron & Ueckermann (Acariformes: Bdellidae), H. quercusi Eghbalian, Khanjani, Safaralizadeh, Ueckermann sp. nov., and a new species of Neomolgus Oudemans, N. iraniensis Eghbalian, Khanjani, Safaralizadeh, Ueckermann sp. nov., are described and illustrated. A key is provided for adult females of all known species of Hexabdella, as well as for adult females of Neomolgus from Asian and neighbouring countries, including Iran, Japan and the Siberian region of Russia. All specimens were collected from soil and litter under oak trees, Quercus brantii Lindley (Fagaceae), or from soil and litter under wild almond, Amygdalus scoparia L. (Rosaceae), from western Iran.